Attention deficit hyperactivity disorder in children in the digital age: The impact of electronic screens (Research, Society and Development, 2023)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) associated with the exacerbated use of electronic screens in children has shown worsening symptoms, increased irritability and loss of control, leading to addictions to digital media, as the child population spends more time on the digital network and has less ability to control its use. It is therefore of the utmost importance to understand how the use of the internet and other digital media during the development phase, for prolonged periods, can have an influence on ADHD, since it directly interferes with learning and can extend into adulthood, as well as hindering the development of interpersonal relationships. The aim of this study is to raise awareness and provide information about one of the main detriments to neurological development caused by the abusive use of screens by children. Methodology: This is an integrative literature review carried out using the Scielo and PubMed databases containing publications from 2016 to 2022. Results: In order to fulfill the central objective of this article, 20 articles were selected that were consistent with the theme. Conclusion: In view of the above, it is necessary to intensify multidisciplinary intervention and family mediation to control screen exposure time, thus making it possible to improve the quality of life of individuals with ADHD.